Institut Tadbiran Awam Negara (INTAN): Asset Management System / Audrey Laurentius - Laurentius, Audrey (University Technology MARA, 2012)
INTAN has evolved over the years in to a centre of excellence for the training of Malaysian public officials in order to meet the challenges of a nation moving rapidly towards a developed nation status. A framework encompassing four pillars of national transformation has been constructed by the government in order to move the country forward and achieve Vision 2020. INTAN, as the premier training arm of the Public Service Department of Malaysia, has taken the leading role in transforming and enhancing public sector capabilities and effectiveness through its various training programmes and initiatives. Within the Civil service, change is underway in learning and development too. INTAN’s main core business is to enhance the development of human capital in the public sector and will help deliver greater value from learning and development. This organization’s major role is to disseminate skill and knowledge through its numerous training programmes and activities. INTAN will also try to develop the right attitude towards public sector transformation. The mission of INTAN is to develop talented and “thinking civil servants” with the aim of creating public sector officers who are knowledgeable, skilled, creative and innovative. Apart from that, INTAN also has a unique window into the public service, with access to decision-makers and specialists who have in-depth knowledge of government priorities and learning requirements. Relevant learning opportunities are made available by drawing on the insiders’ view. Colleagues from across departments and agencies can be brought together, from coast to coast, in the classroom and online. INTAN, with the cooperation of the Public Services Department, have played crucial roles in not only providing civil servants with the necessary facilities and training, but also scholarships, allowances, grants, and so on, for further education and career advancement (Jeong, 2007).